ANAMU, MORINGA, SPIRULINA, AND CHLORELLA: CONTRIBUTION TO THE QUALITY OF LIFE OF ONCOLOGY PATIENTS – RESULTS OF THE POST-MARKETING PROSPECTIVE STUDY PERFORMED IN SERBIA IN 2021 – 2022 - Estevez Garcia, Anabely; Kovčin, Vladimir; Venegas Godinez, Aliuska (Srpski medicinski časopis Lekarske komore, 2023)
Introduction: The quality of life is one of the priority goals in the treatment of oncology patients. In addition to conventional therapies, symptomatic and supportive treatments are valuable for the final treatment outcome. Many such patients resort to alternative methods, such as herbal therapy.Study aim: This prospective study aimed to assess the effect of the plants: anamu, moringa, spirulina, and chlorella, which are routinely used in Cuba, on the quality of life of oncology patients.Materials and methods: Forty-six patients with various stage four malignant tumors were examined. Of the 46 patients, 26 were on chemotherapy, while 18 were on symptomatic and supportive therapy. The patients used extracts of the afore-mentioned plants orally, for three months. With prior consent and authorization, the standard EORTC QLQ-C30 questionnaire, written in the patients' native language, was used to assess quality of life, before and after three months of use.Results: According to patient ratings, overall assessment of patient general health status and quality of life showed significant improvement after three months of use of the extracts, as compared to the beginning of application. According to the questionnaire, all five parameters improved on the functional scale (Table 2, Graph 2), (p = 0.0002338), and the scores on the symptoms scale also improved (fatigue, p = 0.01501; pain, p = 0 ,0436). Women achieved better physical functionality and significant loss of fatigue and pain, while cognitive functionality improved in men. Emotional functionality improved in the subgroup of patients who were receiving chemotherapy, while in those who had previously received chemotherapy, there were significant differences in the symptoms scale score regarding loss of appetite and constipation – symptoms that resolved after three months of product use, thus equating the subgroups in terms of the reduction of these symptoms. In other functional parameters, statistically significant differences were also obtained for all patients.Conclusion: The improvement in the quality of life and functionality of patients, as well as the reduction in symptoms, whether the patients received chemotherapy or not, was statistically significant.
Keywords: malignant tumors; quality of life; anamu; chlorella; moringa; spirulina